Health economic evaluation of EV71 vaccination in children under the school-age population in Guangdong Province, China - Zhang, Hui; Zheng, Jienan; Luo, Danxia; Zeng, Biao; Yi, Yao; Yang, Fen; Lin, Lilin; Deng, Aiping; Kang, Min; Zhang, Yingtao (Frontiers in Public Health, 2025)
BackgroundThis study aims to evaluate the health economics of hand-foot-mouth disease enterovirus 71 (EV71) vaccination for the population of appropriate age in Guangdong Province.MethodsA SEIR model was constructed, and a group of differential equations was established. The incidence data of HFMD in Guangdong from January to June 2017 were used to fit the model and the basic reproduction value (R0) of this disease was simulated. Then, the incidence of HFMD under different vaccination coverage rate (0, 40, 70, and 90%) was simulated in four scenarios. Cost-effectiveness analysis was used to evaluate the health economics.ResultsThe self-funded voluntary EV71 vaccination strategy implemented in Guangdong Province has effectively reduced the disease economic burden of EV71-type HFMD, and the disease economic burden saved during the peak seasonal segment of HFMD in 2017 was $1,080,000. Meanwhile, Scenario 2, 3, and 4 would each result in a cumulative reduction of 6,525, 9,556, and 10,989 confirmed cases, respectively, with net monetary benefits of approximately $6.55 million, $9.59 million, and $11.2 million. The study results show that the current vaccine pricing is not cost-effectiveness, while the vaccine price is lower than $13.15, EV71 vaccination in Guangdong Province has a cost-effectiveness advantage.ConclusionVaccination can reduce the incidence of HFMD caused by EV71, which helps to improve the status of HFMD and decreases the disease burden.